The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13019-019-0998-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mild renal dysfunction on isolated cardiopulmonary coronary artery bypass grafting: a retrospective propensity score matching analysis

Abstract: BackgroundMild preoperative renal dysfunction (RD) is not rare in patients receiving isolated cardiopulmonary coronary artery bypass grafting (CCABG). However, there are not too many studies about the impact of mild preoperative RD on in-hospital and follow-up outcomes after isolated CCABG. This single-centre, retrospective propensity score matching study designed to study the impact of mild preoperative RD on in-hospital and long-term outcomes after first isolated CCABG.MethodsAfter propensity score matching,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
2
1
0
1
Order By: Relevance
“…Cox regression manifested that postoperative in-hospital AKI was a significant variable related to the new onset of dialysis and long-term mortality, and the HR was 1.83 and 1.31 respectively (95%CI 1.12–2.86, p = 0.007; 95%CI 1.17–2.58, p = 0.015). This study was consistent with our previous study and some other studies which demonstrated that development of AKI was associated with high short-term and long-term morbidity and mortality [ 18 , 26 ]. AKI has been associated with progression to chronic kidney disease(CKD) and dialysis in many reports [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…Cox regression manifested that postoperative in-hospital AKI was a significant variable related to the new onset of dialysis and long-term mortality, and the HR was 1.83 and 1.31 respectively (95%CI 1.12–2.86, p = 0.007; 95%CI 1.17–2.58, p = 0.015). This study was consistent with our previous study and some other studies which demonstrated that development of AKI was associated with high short-term and long-term morbidity and mortality [ 18 , 26 ]. AKI has been associated with progression to chronic kidney disease(CKD) and dialysis in many reports [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…Cox regression manifested that postoperative in-hospital AKI was a signi cant variable related to the new onset of dialysis and long-term mortality, and the HR was 1.83 and 1.31 respectively (95%CI 1.12-2.86, p=0.007; 95%CI 1.17-2.58, p = 0.015). This study was consistent with our previous study and some other studies which demonstrated that development of AKI was associated with high short-term and long-term morbidity and mortality [18,27] . AKI has been associated with progression to chronic kidney disease(CKD) and dialysis in many reports [28] .…”
Section: Long-term Outcomessupporting
confidence: 94%
“…ОПП, развившийся после АКШ, сопряжен с неблагоприятным прогнозом в раннем послеоперационном периоде, с ухудшением прогноза и качества жизни после выписки из стационара, а также высокой летальностью [5]. Применение ИК во время операций на открытом сердце является фактором риска развития ОПП, поскольку его использование ассоциировано с развитием воспалительной реакции, почечной гипоперфузией, гипотермией, гемодилюцией, а также с отсутствием пульсирующего кровотока [14]. В настоящее время остается открытым вопрос, может ли техника проведения ИК улучшить результаты АКШ.…”
Section: Introductionunclassified